Impact of Australian Bureau of Statistics data perturbation techniques on the precision of Census population counts, and the propagation of this impact in a geospatial analysis of high-risk foot hospital admissions among an Indigenous population. Issue 1 (2nd January 2022) - Kok, Mei Ruu; Tuson, Matthew; Turlach, Berwin; Boruff, Bryan; Vickery, Alistair; Whyatt, David
ABSTRACT: Precise population counts facilitate reliable estimation of differences in disease risk between population sub-groups or geographic regions, which informs rational public health decision-making. In Australia, Census population counts obtainable via the Australian Bureau of Statistics' (ABS') TableBuilder tool, which are widely used, are routinely perturbed to protect privacy. We examine this perturbation's impact on: the precision of TableBuilder population counts, and a geospatial analysis of high-risk foot (HRF) hospital admissions among Western Australian (WA) Indigenous people. The former is severely compromised, disproportionately so for Indigenous people and under the currently employed 'perturbation without additivity' (PWoA) approach. E.g., based on fine-resolution, PWoA-affected data, the Indigenous population total for 'Inner City' WA was >50% lower than its true total. Imprecise calculation of WA Indigenous HRF admission counts, and misrepresentation of high-rate regions of such admissions in Perth, resulted. An approach suggested to manage this - examination of coarse-resolution data - is inadequate, partly due the modifiable areal unit problem. However, a novel map overlay technique alleviates this issue. We recommend that the ABS review the PWoA approach and consider implementing different statistical disclosure control techniques or reverting to the previously employed 'perturbation with additivity' approach, prior to releasing data from the 2021 Australian Census.